Notification of crop varieties and registration of germplasm : Barley Variaty DWRB101 - Kumar, Vishnu (The Indian Journal of Genetics and Plant Breeding, 2016)
DWRB101 (DWR28/BH581) is a new two-row maltÂ barley variety, which was developed using pedigreeÂ method at IIWBR, Karnal. The variety was identified for irrigated timely sown conditions of North WesternÂ Plains Zone (NWPZ) during 53rd All India CoordinatedÂ Wheat and Barley Workerâ€™s meet held at JNKVV, Jabalpur during 22-25 Aug. 2014. The variety wasÂ subsequently released by the â€œCentral Sub-CommitteeÂ on Crop Standards, Notification and Release ofÂ Varieties for Agricultural Crops (CVRC)â€ and notifiedÂ by the Gazette Notification S.O. No. 268 (E) dated onÂ 28th Jan, 2015 for irrigated timely sown conditions ofÂ North Western Plains Zone (NWPZ). DWRB101 wasÂ tested at a total of 31 locations with four checks viz.Â DWRUB52 and DWRB92 (both two-row type) and KÂ 551 and BH 902 (both six-row type) under coordinatedÂ evaluation trials. DWRB101 exhibited average grainÂ yield as 5010 Kg/ha (mean of 31 trials over 3 years).Â DWRB101 depicted superiority in grain yield over tworow malt barley checks DWRUB52 (6.6%), DWRB92Â (4.8%) and six-row checks K551 (15.2%) and BH902Â (7.7%), respectively. DWRB101 was differentiated from DWRUB52 by molecular markers viz. Bmac213,Â Bmag382, HVM40, MWG634, GMS61, Bmag337,Â Bmag500 etc. In agronomical trials, at recommended N dose, the proposed variety DWRB101 showedÂ numerical superiority for grain yield over both two-rowÂ malt barley checks i.e. DWRUB52 (6.88 %) and DWRB92 (1.86%), respectively.